Ensuring Digital Access: Impediments and Potentials for PWDs in Rural E-Governance. - Naik, Arun; Pandey, Santwana; Majhi, Lipun; Seth, Bharati (Journal of Neonatal Surgery, 2024)
India’s digital governance transformation undoubtedly changed the delivery of public service, but according to the Telecom Regulatory Authority of India, only about 34% of rural population had internet access. This study examines how people with disabilities (PWDs) in rural Odisha-specifically in Balangir district, deal with the improving digital technology of government services. The ground study reveals that there are ongoing barriers that prevent PWDs from accessing the most basic digital services, despite the fact that programs like Digital India and state e-governance initiatives guarantee inclusive development. The complex interplay between inadequate infrastructure, inaccessible interface design, low levels of digital literacy and deeply rooted social attitudes that collectively prevent PWDs from engaging with technology in remote and rural areas of Balangir district. Substantial inclusion is made possible by expanding opportunities brought about by mobile technology reach, community-based support systems and enlightened policy environments. Based on empirical study and one to one interaction about individual perspectives, the research contributes to policy discussions by demonstrating how inclusive e-governance can serve as an encouragement for more extensive social transformation, ensuring that India’s digital transformation truly leaves no one behind...